1973
DOI: 10.1002/1097-0142(197312)32:6<1332::aid-cncr2820320607>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of postoperative radiotherapy in hypernephroma treatment—A clinical trial

Abstract: A controlled trial was planned in order to assess the value of postoperative radiotherapy in the treatment of hypernephromata. Crude survival figures, covering 3–12 years following treatment, revealed that those cases treated by surgery only did better than those treated by combined surgery and irradiation, although the results are not statistically significant. Analysis over the first 5 years revealed that the greatest differences in survival between the 2 groups occurred in the first 12 months postoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…Published results are controversial. Finney randomized 52 patients to post-operative radiotherapy with a total dose up to 55 Gy and 48 patients to no further therapy [10,12]. Radiation therapy did not result in an overall survival advantage and had no impact on the local recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published results are controversial. Finney randomized 52 patients to post-operative radiotherapy with a total dose up to 55 Gy and 48 patients to no further therapy [10,12]. Radiation therapy did not result in an overall survival advantage and had no impact on the local recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of beneficial effects of radiation therapy after nephrectomy come from non-randomized trials [5 -9]. In contrast, a few randomized studies found no benefit from post-operative radiotherapy [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…28 A similar trial performed even earlier, in the 1970s, also did not find a benefit from postoperative radiation therapy. 29 Some other studies explored the role of hormone therapies, with disappointing results. One prospective multicenter study compared medroxyprogesterone acetate treatment for 1 year versus no treatment after radical nephrectomy, and failed to demonstrate any benefit in survival.…”
Section: Other Treatment Modalitiesmentioning
confidence: 99%
“…Until the eighties, attempts to treat widespread diseases were not successful and renal cancer is considered as a radio-resistant and chemoresistant tumour (Finney, 1973;Droz et al, 1988 The characteristics of the 25 eligible patients are detailed in Table I. There were 16 males and nine females; median age was 69 (range 65-77).…”
mentioning
confidence: 99%
“…the highest incidence occurs at 65 years of age and 50 to 60% of the patients develop distant metastases (Holland, 1977;Ritchie et al, 1987). Until the eighties, attempts to treat widespread diseases were not successful and renal cancer is considered as a radio-resistant and chemoresistant tumour (Finney, 1973;Droz et al, 1988).…”
mentioning
confidence: 99%